Intake of lead (Pb) from tap water of homes with leaded and low lead plumbing systems - Jarvis, Peter; Quy, Katie; MacAdam, Jitka; Edwards, Marc; Smith, Marjorie (Elsevier, 2018)
Methods of quantifying consumer exposure to lead in drinking water are increasingly of interest worldwide, especially those that account for consumer drinking habits and the semi-random nature of water lead release from plumbing systems. A duplicate intake protocol was developed in which individuals took a sub-sample from each measured drink they consumed in the home over three days in both winter and summer. The protocol was applied in two different water company regional areas (WC1 and WC2), selected to represent high risk situations in England, with the presence or absence of lead service pipes or phosphate corrosion control. Consumer exposure to lead was highest in properties with lead service pipes, served by water without P dosing. The protocol indicated that a small number of individuals in the study, all from homes with lead service pipes, consumed lead at levels that exceeded current guidance from the European Food Standards Agency. Children's potential blood lead levels (BLLs) were estimated using the Internal Exposure Uptake Biokinetic model (IEUBK). The IEUBK model predicted that up to 46% of children aged 0–7 years old may have elevated BLLs (>5 μg/dL) when consuming the worst case drinking water quality (>99%ile). Estimating blood lead levels using the IEUBK model for more typical lead concentrations in drinking water identified in this study (between 0.1 and 7.1 μg/L), predicts that elevated BLLs may affect a small proportion of children between 0 and 7 years old.
Keywords: Drinking water; Intake; Lead; Phosphate; Plumbosolvency